Human adipose mesenchymal stem cell-derived exosomes alleviate fibrosis by restraining ferroptosis in keloids - Tian, Yuan; Li, Meijia; Cheng, Rong; Chen, Xinyue; Xu, Zhishan; Yuan, Jian; Diao, Zhiyong; Hao, Lijun (Frontiers in Pharmacology, 2024)
Background: Keloid is a fibroproliferative disease with unsatisfactory therapeutic effects and a high recurrence rate. exosomes produced by adipose-derived mesenchymal stem cells (ADSC-Exos) have attracted significant interest due to their ability to treat fibrosis. However, the molecular mechanisms of ADSC-Exos in keloids remain inconclusive.Objective: Our study revealed the relationship between ferroptosis and fibrosis in keloids. Subsequently, this study aimed to explore further the anti-fibrotic effect of ADSC-Exos on keloids through ferroptosis and the potential underlying mechanisms.To investigate the impact of ferroptosis on keloid fibrosis, Erastin and ferrostatin-1 (fer-1) were utilized to treat keloid fibroblast. Keloid keloids treated with Erastin and fer-1 were cocultured with ADSC-Exos to validate the impact of ferroptosis on the effect of ADSC-Exos on keloid anti-ferrotic protein, peroxidase 4 (GPX4) and anti-fibrotic effects in vivo and in vitro by Western blot, as well as variations in iron metabolite expression, malondialdehyde (MDA), liposomal peroxidation (LPO) and glutathione (GSH) were analyzed. The effect of solute carrier family 7-member 11 (SLC7A11) silencing on ADSC-Exo-treated keloid fibroblast was investigated.Results: Iron metabolite dysregulation was validated in keloids. Fibrosis progression is enhanced by Erastin-induced ferroptosis. The anti-fibrotic effects of ADSC-Exos and fer-1 are related to their ability to prevent iron metabolism. ADSC-Exos effectively suppressed keloid fibrosis progression and increased GSH and GPX4 gene expression. Additionally, the use of Erastin limits the effect of ADSC-Exos in keloids. Furthermore, the effect of ADSC-Exos on keloids was associated with SLC7A11-GPX4 signaling pathway.We demonstrated a new potential mechanism by which anti-ferroptosis inhibits the progression of keloid fibrosis and identified an ADSC-Exo-based keloid therapeutic strategy. Resisting the occurrence of ferroptosis and the existence of the SLC7A11-GPX4 signaling pathway might serve as a target for ADSC-Exos.